Implementasi Fungsi-Fungsi Kepemimpinan Kepala Distrik - Alexander Phuk Tjilen; Hubertus Oja (Universitas Musamus,Merauke,Papua, 2019)
The study aims to provide an overview of how to implementing the functions of district leaders in the Boven Digoel Regency in carrying out their duties. The method used is descriptive qualitative, where data is obtained from interviews and surveys in the field. The results of this study, implementation of the function of the district head in general government affairs and community participation to improve the community's economy is not optimally constrained by the ability to coordinate, the readiness of the organizational structure and the available budget. Efforts to public order and enforcement of regional regulations are helped from a conducive situation in the community and contributions from the instances of the services and security forces